Quasi-one-dimensional phosphorene nanoribbons grown on silicon by space-confined chemical vapor transport. Issue 17 (31st January 2023) - Du, Kaixiang; Wang, Mingyuan; Liang, Zhiping; Lv, Quanjiang; Hou, Haigang; Lei, Shuangying; Hussain, Shahid; Liu, Guiwu; Liu, Junlin; Qiao, Guanjun
Abstract : In this work, we present a strategy for the space-confined chemical vapor transport synthesis of quasi-one-dimensional surface-passivated monocrystalline PNRs on a silicon substrate. Abstract : Phosphorene nanoribbons (PNRs) combine the flexibility of one-dimensional (1D) nanomaterials with the large specific surface area and the edge and electron confinement effects of two-dimensional (2D) nanomaterials. In spite of the substantial advances in bulk black phosphorus (BP) manufacturing, achieving PNRs without degradation is still a big challenge. In this work, we present a strategy for the space-confined chemical vapor transport synthesis of quasi-one-dimensional surface-passivated monocrystalline PNRs on a silicon substrate. The growth mechanism of the PNRs is proposed by combining experimental results and DFT calculations, indicating that the P4 molecules can break, restructure, and epitaxially nucleate on the surface of the Au3 SnP7 catalyst, and finally prefer to grow along the zigzag (ZZ) direction to form PNRs. The low gas flow rate and an appropriate phosphorus molecule concentration allow the growth of PNRs with structural integrity, which can be regulated by the amount of red phosphorus and the confined space.